Effect of lactic threshold training on the development of some functional lung indicators and achievement of 800 meter runners under 20 years old - Jawad Mohammed, Zaydoon; Sabah Abdulsalam, Zahia (International Journal of Psychosocial Rehabilitation, 2020)
The process of preparing the physical and functional public and private for runners of intermediate distances is to give them a certain amount of of each of the aerobic and anaerobic energy in different proportions according to the requirements of specialized effectiveness; that is, the longer the race distance, the greater the need for a high level of aerobic energy, and vice versa, the shorter the race distance, the more it goes to training anaerobic energy. The effectiveness of running 800 meters in competitions is something most athletics coaches find difficult to develop. It is good, given the need for hostility in this competition, to develop all energy systems, specifically the non-tactical system. The research aims to prepare (tactical threshold) exercises for young players with an effectiveness of 800 m and to identify the effect of non-tactical threshold exercises in the development of some functional variables of the lungs and the achievement of an aggressive 800 m youth. The researcher used the experimental approach for its suitability to the nature of the research. The research community was determined by young players in elite clubs of ages 16-18 years for the training season 2017-2018, which numbered 14 players. As the research sample was chosen using the comprehensive inventory method, the sample was divided into two groups (experimental and controlling), and by seven players for each group. The most important conclusions were reached and they produced the tactical threshold exercises that were carried out from the experimental group that used a remarkable development in the achievement of the 800-meter enemy. Lactic threshold exercises also caused an increase in all lung function variables, part of which elevated to the level of significance (forced vital amplitude, forced expiratory volume for one second, and maximum lung ventilation volume).